Enhancement of photodetection characteristics of MoS2 field effect transistors using surface treatment with copper phthalocyanine. Issue 44 (27th October 2015) - Pak, Jinsu; Jang, Jingon; Cho, Kyungjune; Kim, Tae-Young; Kim, Jae-Keun; Song, Younggul; Hong, Woong-Ki; Min, Misook; Lee, Hyoyoung; Lee, Takhee
Abstract : We fabricated the hybrid MoS2 photodetector by stacking copper phthalocyanine. This hybrid photodetector exhibited better performance compared with pristine MoS2 photodetectors. Abstract : Recently, two-dimensional materials such as molybdenum disulfide (MoS2 ) have been extensively studied as channel materials for field effect transistors (FETs) because MoS2 has outstanding electrical properties such as a low subthreshold swing value, a high on/off ratio, and good carrier mobility. In this study, we characterized the electrical and photo-responsive properties of MoS2 FET when stacking a p-type organic copper phthalocyanine (CuPc) layer on the MoS2 surface. We observed that the threshold voltage of MoS2 FET could be controlled by stacking the CuPc layers due to a charge transfer phenomenon at the interface. Particularly, we demonstrated that CuPc/MoS2 hybrid devices exhibited high performance as a photodetector compared with the pristine MoS2 FETs, caused by more electron–hole pairs separation at the p–n interface. Furthermore, we found the optimized CuPc thickness (∼2 nm) on the MoS2 surface for the best performance as a photodetector with a photoresponsivity of ∼1.98 A W −1, a detectivity of ∼6.11 × 10 10 Jones, and an external quantum efficiency of ∼12.57%. Our study suggests that the MoS2 vertical hybrid structure with organic material can be promising as efficient photodetecting devices and optoelectronic circuits.